PRAGMATYZACJA ŚWIADOMOŚCI I PLURALIZM STRATEGII PRZYSTOSOWAWCZYCH POLAKÓW W LATACH 1988 - 1999 - Ziółkowski, Marek (Wydział Prawa i Administracji UAM, 1999)
The article is based on results of empirical research work done in Poland in 1988, 1993 and 1998 - which referred to changes within perception of the reality, to changes in consciousness of the Polish society and, finally, to changes in adapting strategies o f this society within the period of radical reconstruction of economic and political system of the country. New order has created many quite new chances but, in the same time, has deprived many people of hitherto existing assurances and became a source of great number of threats. Poles are characterised with many-sidedness, plurality and instrumentalisation of their life-strategies; among them - old strategies (i.e. known under former system) get mixed and necessarily broken by strategies of new kind which are a result of acceptation or - at least - o f adapting to the rules typical for new order. Polish society is nowadays much more reflective than once (so, it is constantly considering what is really going on and - what could be done indeed) and the fact is that it is a society which is having recourse to a steady comparison of itself (principally - with Western culture and economies). Furthermore, Poles are a society which is rather quite impatient; they desire to quickly touch positive effects of changes introduced and, of course, of their own relinquishments suffered on this occasion. Lack o f rapid results in this matter can on one hand lead to stimulate increased activity of an individual but, on the other, pushes often to frustration and discouragement, too.
PRAGMATISATION OF CONSCIOUSNESS AND PLURALITY OF ADAPTING STRATEGIES OF POLES IN 1988-1999